The impact of public participation in constitution making - Hudson, Alexander Edward (2018)
Public participation has long been an important element of constitution-making processes. It increasingly takes place early in the process, ostensibly offering citizens an opportunity to contribute directly to the text of their new national charter. Despite growth in the use and political prominence of participatory mechanisms, we know little about their effects. This dissertation argues that the impact of public participation on the text of constitutions is small in almost all cases, but that there are systematic ways in which this impact varies. Specifically, the variation in the effects of public participation is for the most part determined by the strength of political parties in the constitution-making process. In constitution-making bodies where there are strong parties, there is very little room for effective public participation. In such systems, there will be almost no impact from public participation, even where significant amounts of time and money are devoted to facilitating it. Conversely, in constitution-making bodies where political parties are not present, or where parties are weak, there will be a greater impact from public participation, as drafters are unprotected from pressure groups and also more reliant on the information they provide. I further argue that the informational challenges of assessing the impact of public participation prevent the majority of participants from determining whether or not the participation program was effective. Thus, public participation programs can serve to increase public support for a constitution even when drafters do not make any changes to the content of the constitution in response to public input. This theory is tested through studies of three cases of highly participatory constitution making. Keeping the level and means of participation relatively constant, the three cases have been chosen to include a case with strong parties (South Africa), a case with weak parties (Brazil), and a case where the constitution was drafted without parties (Iceland). As predicted, the South African case shows negligible impacts from public participation, Brazil has some scattered impacts, and Iceland shows high levels of impact. The findings here demonstrate that the expected relationships between citizens, political parties, and interest groups exist even in constitution-making processes. Moreover, it shows that there are trade-offs between stability, textual quality, and more effective public input. Government